Effect of pasture on chestnut woods on meat quality and fatty acid composition of fat in Cinta Senese pigs - Pugliese C.; Pianaccioli L.; Sirtori F.; Acciaioli A.; Bozzi R.; Franci O. (5. International Symposium on the Mediterranean Pig, 2007)
Seven Cinta Senese pigs were reared in a paddock and fed on barley; other 7 pigs were reared in the woods and fed on chestnuts. A sample cut was removed from the loin and dissected. The following analyses were carried out on Longissimus lumborum (LI): colour measurements, moisture, intramuscular fat, water-holding capacity and shear force. Colour measurements and total fatty acids were determined on subcutaneous fat. As sample cut composition is concerned, no differences were found for total lean, Ll and Psoas major percentages but pig fattened with chestnut showed a higher percentage of subcutaneous fat (41.7 vs 37.6%) due to the more important development of the inner layer. The a*, b* and chroma values were lower in pigs fattened with chestnut (3.45 vs 4.83; 3.83 vs 5.19; 5.17 vs 7.11 respectively). The chestnut diet registered higher MUFA (48.9 vs 47.6%), C18:1 (46 vs 44.6%) and PUFA n-3 (1.46 vs 1.2%) contents and a lower thrombogenicity index (0.944 vs 0.999).
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)